A hydrogel based herbal nanoformulation for enhanced wound healing - Shaheen Sultana; Nada Alzahrani; Reem Alzahrani; Wejdan Alshamrani; Waad Aloufi; Maria Khan; Mohammad Yusuf (Brazilian Journal of Pharmaceutical Sciences)
Abstract The aim of the present study is to develop a chitosan based herbal formulation using rhubarb for wound healing. Wound healing is a dynamic process facilitating the regeneration or repair of broken tissue. Rhubarb is commonly used worldwide for their effective antiseptic, antifungal and antiviral properties. Rhubarb loaded chitosan nanoparticles were prepared by ionic cross-linking process with sodium lauryl sulphate. The optimized formulation was examined for antibacterial activity against S. aureus and P. aeruginosa. Wound healing effects of the developed formulation was studied on excision wound model in Wistar albino rats. Average particle size and zeta potential of chitosan nanoparticles varied from 93 to 2,225 nm and from+30.82 to -16.08 mV, respectively. On the basis of particle size, zeta potential, and % entrapment, Formulation C 4 (0.0595% chitosan, 0.535% cross-linker, and 1% drug) was selected among different checkpoint formulation and further studies were performed. Hydrogel was developed using a combination of polyvinylpyrrolidone and carboxymethyl cellulose. Nanoformulation based hydrogel showed significantly enhanced antimicrobial activity against tested pathogenic microbial strains in comparison to drug solution, as well as marketed formulations.